Effects of ultrasound treatment on the physicochemical and emulsifying properties of proteins from scallops (Chlamys farreri). (April 2019) - Wu, Di; Wu, Chao; Ma, Wuchao; Wang, Zhenyu; Yu, Cuiping; Du, Ming
Abstract: In this study, different ultrasound powers, namely, 0, 200, 400, 600, 800 and 950 W with intensities of 0, 707.71, 1415.43, 2123.14, 2830.86 and 3361.64 W cm −2, respectively, were applied to treat proteins from scallops. Proteins from scallops ( C. farreri ) (ScP) were obtained by alkali dissolution and acid deposition. Changes in the particle size, surface hydrophobicity, sulfhydryl group content, and emulsifying properties were investigated. With the increasing ultrasonic power, ScP has better disposability. Compared with other treatments, ScP treated by a 950 W ultrasound had smaller particles, a higher surface hydrophobicity index (H0 ) (476.73 ± 3.52), a higher free SH group (2.19 ± 0.05 μmol/g protein) and a higher nitrogen solubility index (NSI) (93.96 ± 0.52%). SDS-PAGE showed that the ultrasound could not change the molecular weight distribution of ScP. Secondary structural analysis by circular dichroism indicated that a high power ultrasound treatment could decrease the random coil and α-helix constituents and increase the β-sheet constituent of ScP. Confocal laser scanning microscopy (CLSM) showed that the emulsion stability was increased by the ultrasound treatment. It was concluded that the ultrasound treatment has beneficial effects with respect to the physiochemical and emulsifying properties of ScP and promotes its potential industrial applications. Graphical abstract: Highlights: Ultrasound treatment could reduce the particle size of CFP molecules. A sharp increase of H0 was found after ultrasound treatment. A uniform dispersion of CFP emulsion was visualized after ultrasound treatment. The protein distributions between the cream and aqueous phase were different.